Polypyrrole zinc-doped film deposited on a plasma-treated surface improves the tribocorrosion behavior of titanium dental implant material - Borges, Maria Helena R.; Kanniyappan, Hemalatha; Sun, Yani; Nagay, Bruna Egumi; da Cruz, Nilson C. [UNESP]; Mathew, Mathew T.; Barão, Valentim A.R. (Elsevier, 2023)
Polypyrrole (PPy) films have shown attractive electrochemical properties and promising implant applications when electrodeposited on plasma electrolytic oxidation (PEO) surfaces. Although the PEO + PPy surface demonstrates excellent mechanical and electrochemical performance, there are no reports on the effects of combined corrosion and mechanical interactions, which simulates the oral environment. In addition, since implant failures may be related to deficiencies in the osseointegration process, the electrodeposition of zinc (Zn) on the coating can promote an osteogenic substrate. Therefore, we aimed to investigate the tribocorrosion behavior of PEO-treated surfaces coated with PPy films with and without Zn and whether such PPy films affect the cellular response of MG-63 human osteoblast-like cells. Titanium discs with machined and PEO-modified surfaces were considered as controls. The experimental groups used PEO surfaces followed by electrodeposition of PPy (PEO + PPy) and PPy and Zn (PEO + PPy/Zn). The surfaces' physical-chemical properties were assessed. The tribocorrosion tests were run under free potential and potentiostatic (anodic and cathodic potentials) conditions using a pin-on-disk tribosystem simulating the oral environment (load = 1 N, stroke = 2 mm, number of cycles = 2000). Electrochemical impedance spectroscopy was performed before and after tribocorrosion to analyze the changes in corrosion kinetics. Worn areas were observed using white-light-interferometry and scanning electron microscopy. For in vitro cell experiments, the viability, number of live/dead cells, adhesion ability, and mineralization property of cells were evaluated. Our outcomes revealed that PPy films improved tribocorrosion performance by exhibiting more positive OCP values and slight fluctuation and variation of the current value during the sliding phases. In general, due to the films' morphology and “cushion effect”, PPy films enhanced the surface resistance against corrosion and wear, indicating a low total weight loss (Kwc) and wear-corrosion degradation mechanism. The PEO + PPy/Zn surface was cytocompatible, enhancing the cell adhesion and proliferation on the surface. Overall, PPy films represent a promising coating to improve the stability and lifetime of biomedical implants.
Keywords: Biocompatibility; Dental implants; Polypyrrole; Surface treatment; Tribocorrosion